Hierarchy and Plasticity in the Intestinal Stem Cell Compartment. Issue 10 (October 2017) - Yousefi, Maryam; Li, Linheng; Lengner, Christopher J.
Abstract : Somatic stem cells maintain tissue homeostasis by organizing themselves in such a way that they can maintain proliferative output while simultaneously protecting themselves from DNA damage that may lead to oncogenic transformation. There is considerable debate about how such stem cell compartments are organized. Burgeoning evidence from the small intestine and colon provides support for a two-stem cell model involving an actively proliferating but injury-sensitive stem cell and a rare, injury-resistant pool of quiescent stem cells. Parallel with this evidence, recent studies have revealed considerable plasticity within the intestinal stem cell (ISC) compartment. We discuss the evidence for plasticity and hierarchy within the ISC compartment and how these properties govern tissue regeneration and contribute to oncogenic transformation leading to colorectal cancers. Trends: Parallels between the long-term hematopoietic stem cell and the reserve intestinal stem cell (ISC) are emerging. At least two robust populations of ISCs contribute to homeostasis: WntHigh active ISCs and WntNegative quiescent reserve ISCs. Genetic ISC-proxy reporter alleles mark heterogeneous populations of cells. Plasticity can be observed in more committed epithelial cells on return to a vacated crypt base niche. Reserve ISCs exist primarily in G0 and are able to reenter the cell cycle, while long-term (≥1 month) label-retaining cells are arrested in G1 and cannot.